Experimental diabetic nephropathy in rats injected with alloxan - Ibrahim Mustafa, Bushra (The Iraqi Journal of Veterinary Medicine, 1996)
The present investigation aimed determenation of diabetic nephrepathy in alloxan treated rats. The study included: Seruim chemical studies. Histopathological and histochemical study on the kidney glomeruli. Thirty white male rats were used. They were randomly allocated into 3 groups. Izgroup was injected with alloxan monohydrate for 30 days: 2nd group was fed 1% cholesterd lie and injection of 38 mg/kg B.W alloxan dialy for 30 days; 3rd group was normal diet. kept on Blood glucose and total Serum cholestered in 1 and 2 groups significantly increased at day 10, 20, 30. Glomerular lesion in 1 and 2 groups were found, characterized by dilation of glomeruli which showed lipid accumulation. In conclusion, hyperlipidemia accompanying hyperlipidemia in alloxan induced hyperglycemia, in part apossible factor in the pathogenesis of diabetic nephropathy.